Local treatment with ultrasound-guided methotrexate in interstitial ectopic pregnancy: Clinical case - Carpio Guzmán, Luis (2024)
Introduction: Interstitial ectopic pregnancy is a rare condition with increasing incidence due to assisted reproductive treatments and prior tubal surgeries. Case presentation: This report describes the case of a 34-year old patient with a history of bilateral adnexectomy due to borderline ovarian cancer, who developed an interstitial ectopic pregnancy following in vitro fertilization with donated eggs. Management involved a minimally invasive approach with ultrasound-guided intrasac methotrexate injection at a dose of 1 mg/kg. The patient remained clinically stable, experienced mild hypogastric pain, and showed a progressive decrease in beta-hCG levels, confirming treatment success. Conclusion: This case underscores the role of transvaginal ultrasound as a pivotal tool for early diagnosis and conservative management, aimed at uterine preservation and fertility.